1999
DOI: 10.1046/j.1365-2672.1999.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Candida krusei strains from spontaneously fermented maize dough by profiles of assimilation, chromosome profile, polymerase chain reaction and restriction endonuclease analysis

Abstract: A .E . H A YF OR D AN D M . JA KO B SE N. 1999. Several isolates of Candida krusei from indigenous spontaneously fermented maize dough have been characterized for the purpose of selecting appropriate starter cultures and methods for their subspecifies typing. The present work describes the occurrence of C. krusei in Ghanaian fermented maize dough. For detailed pheno-and genotyping, 48 representative isolates were selected and comparison was made with clinical isolates of C. krusei and reference cultures. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Previous work by Hayford and Jakobsen (1999), Hayford and Jespersen (1999) and Hayford et al (1999) have confirmed to species and strain level, the dominant microflora in Ghanaian fermented maize dough to be L. fermentum , S. cerevisiae and C. krusei . The primary fermentation products of heterofermentative lactic acid bacteria include lactic acid, acetic acid and diacetyl (Lindsay 1985).…”
Section: Introductionmentioning
confidence: 74%
“…Previous work by Hayford and Jakobsen (1999), Hayford and Jespersen (1999) and Hayford et al (1999) have confirmed to species and strain level, the dominant microflora in Ghanaian fermented maize dough to be L. fermentum , S. cerevisiae and C. krusei . The primary fermentation products of heterofermentative lactic acid bacteria include lactic acid, acetic acid and diacetyl (Lindsay 1985).…”
Section: Introductionmentioning
confidence: 74%
“…The inadequacy of the use of phenotypic method to differentiate C. inconspicua, C. krusei and C. rugopelliculosa in the previous studies have been responsible for the inability to determine the roles (functional and virulence) of these strains during cassava fermentation. Although, C. rugopelliculosa has been previously used for waste water treatment (Lim, Kim, & Swang, 2003) and strains of C. krusei have been consistently isolated from cassava and cereal fermentation in West Africa (Hayford & Jakobsen, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Different molecular techniques such as PFGE and REA are used for the characterization of Candida. Although this produces high discrimination, these techniques are expensive and laborious (Hayford & Jakobsen, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations